2020
DOI: 10.1097/md.0000000000023439
|View full text |Cite
|
Sign up to set email alerts
|

Detection and diagnostic value of serum NSE and S100B protein levels in patients with seizures associated with mild gastroenteritis

Abstract: Benign convulsions with mild gastroenteritis (CwG) and febrile seizures (FS) associated with mild gastroenteritis are 2 different diseases in the spectrum of seizures associated with mild gastroenteritis. However, specific and useful indicators for the identification of the 2 diseases are lacking. A retrospective analysis was performed to compare the serum neuronal-specific enolase (NSE) and S100B protein levels between patients with these 2 diseases to evaluate the value of NSE and S100B for differential diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
(8 reference statements)
0
3
0
2
Order By: Relevance
“…[74][75][76][77][78] NSE is a -y-subunit of enolase, a major component of the neuronal cytosol. 79) Chen et al 22) compared serum S100B and NSE protein levels in 46 patients with CwG versus 35 patients with febrile convulsions. They found that serum NSE levels were significantly higher in the CwG group than in the febrile seizure group; however, S100B levels were not significantly different.…”
Section: Biomarker For Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…[74][75][76][77][78] NSE is a -y-subunit of enolase, a major component of the neuronal cytosol. 79) Chen et al 22) compared serum S100B and NSE protein levels in 46 patients with CwG versus 35 patients with febrile convulsions. They found that serum NSE levels were significantly higher in the CwG group than in the febrile seizure group; however, S100B levels were not significantly different.…”
Section: Biomarker For Differential Diagnosismentioning
confidence: 99%
“…12,13,18,19) There have also been several recent reports on the diagnosis and treatment of CwG. [20][21][22] Therefore, this review includes recent reports of CwG and covers the epidemiology, clinical manifestations, pathophysiology, biomarkers, and treatment with the aim of promoting the recognition and management of CwG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Поряд із S-100 важливим нейромедіатором є нейронспецифічна енолаза (NSE). Даний протеїн є формою гліколітичного ізоферменту енолази і вважається багатофункціональним білком [12,14,22]. Слід зазначити, що експресується NSE не лише у цитоплазмі ней ронів та нейроендокринних клітинах гіпофізу, а й у щитоподібній залозі, легенях, підшлунковій залозі та кишечнику [12,14], це вказує на його роль у багатьох патологічних процесах.…”
unclassified
“…Даний протеїн є формою гліколітичного ізоферменту енолази і вважається багатофункціональним білком [12,14,22]. Слід зазначити, що експресується NSE не лише у цитоплазмі ней ронів та нейроендокринних клітинах гіпофізу, а й у щитоподібній залозі, легенях, підшлунковій залозі та кишечнику [12,14], це вказує на його роль у багатьох патологічних процесах. На жаль, роботи, присвячені дослідженням ролі S-100 та NSE у процесах цереброінтестинальної взаємодії, досі поодинокі.…”
unclassified